Penggunaan Metode Field Trip Terhadap Hasil Belajar IPS Kelas IV MI Thalabul Khair Kabupaten Banjar - Bainah, Bainah; Huriyah, Huriyah (Jurnal Riset Madrasah Ibtidaiyah, 2024)
Basically, the process carried out consciously by a person to produce change is known as learning behavior and developing positive abilities. One way to facilitate teachers' ability to educate students and achieve learning goals is to use methods. This research aims to determine how field trip learning can improve academic achievement and obtain a significant relationship between student academic achievement and the MI Thalabul Khair field trip learning approach, Banjar Regency. This study uses a quantitative research design. With this design, there is every sample has two classes: a control class and an experimental class. totaling 14 students. Test questions data is gathered by observation, interviews, and documentation, among other techniques. Analyzing the collected data uses hypothesis testing, prerequisite test analysis, and descriptive analysis. This research obtained results, learning through field trips in class IV regarding the surrounding environment in social studies lessons can improve students' academic scores, and social studies learning outcomes are positively correlated utilizing the field trip instructional approach. In accordance with the difference between the control class's average score of 66.42 and the average score of the experimental class of 90.71. The field trip learning method also adds new experiences and enthusiasm to students during the process of learning.